2017
DOI: 10.3389/fnins.2017.00340
|View full text |Cite
|
Sign up to set email alerts
|

Osthole Stimulated Neural Stem Cells Differentiation into Neurons in an Alzheimer's Disease Cell Model via Upregulation of MicroRNA-9 and Rescued the Functional Impairment of Hippocampal Neurons in APP/PS1 Transgenic Mice

Abstract: Alzheimer's disease (AD) is the most serious neurodegenerative disease worldwide and is characterized by progressive cognitive impairment and multiple neurological changes, including neuronal loss in the brain. However, there are no available drugs to delay or cure this disease. Consequently, neuronal replacement therapy may be a strategy to treat AD. Osthole (Ost), a natural coumarin derivative, crosses the blood-brain barrier and exerts strong neuroprotective effects against AD in vitro and in vivo. Recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 62 publications
(88 reference statements)
1
32
0
Order By: Relevance
“…Additionally, we also encapsulated Ost, an effective Chinese medicine monomer for Alzheimer's disease in our previous study. [19][20][21][22][23] It was hypothesized that Tf mediates the transport of Ost-Lip through the BBB via TfRs located on the surfaces of brain capillary endothelial cells, thereby increasing the accumulation of Ost in the brain. Several reports have indicated that Tf-modified liposomes could be used to transport drugs across the BBB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we also encapsulated Ost, an effective Chinese medicine monomer for Alzheimer's disease in our previous study. [19][20][21][22][23] It was hypothesized that Tf mediates the transport of Ost-Lip through the BBB via TfRs located on the surfaces of brain capillary endothelial cells, thereby increasing the accumulation of Ost in the brain. Several reports have indicated that Tf-modified liposomes could be used to transport drugs across the BBB.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Current research indicates that Ost has an improved effect on degenerative diseases of the central nervous system, such as Alzheimer's disease. [21][22][23] Ost can partially pass through the BBB as a small fatsoluble molecule, but its neuroprotective efficacy is limited by its poor solubility, poor stability, poor brain targeting, and low bioavailability. 24 Liposomes, nanoparticles, microspheres, and other nano-drug carriers are considered to be effective methods for the improvement of the bioavailability of Ost.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, microglial activation and proliferation is an important mechanism for the progressive development of epilepsy and its inhibition could be an opportune target for alleviating post-epileptic injury. osthole can cross the blood-brain barrier and exert neuroprotective effects against alzheimer's disease, traumatic brain injury and transient cerebral ischemia (12,25). luszczki et al (26), observed that osthole suppresses seizure activity in a mouse maximal electroshock-induced seizure model.…”
Section: Discussionmentioning
confidence: 99%
“…Osthole can cross the blood-brain barrier and exert neuroprotective effects against Alzheimer's disease, traumatic brain injury and transient cerebral ischemia ( 12 , 25 ). Luszczki et al ( 26 ), observed that osthole suppresses seizure activity in a mouse maximal electroshock-induced seizure model.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [45] demonstrated a protective role of Osthole in the neuronal synapse, since it significantly increased the expression of miR-9 in APP-overexpressed cells [45]. Later on, they hypothesized a cross-talk between miR-9 and the Notch signaling pathway in AD models and observed that Osthole may promote the NSCs differentiation via the upregulation of miR-9 and the subsequent inhibition of the Notch signaling pathway in APP-expressing cells [54]. Jiao et al [48] reported a neuroprotective activity of Osthole that involves the upregulation of miR-107 in AD.…”
Section: Alzheimer's Diseasementioning
confidence: 99%